Investigating the Influence of Functional Units on the Life Cycle Assessment of Asphalt Pavements - Gouveia, Bruno G.; Donato, Marina; Corrêa do Nascimento, Filipe A.; da Silva, Marcelino A. V. (Civil Engineering Journal, 2025)
The Life Cycle Assessment (LCA) of asphalt pavements is an essential tool for reducing environmental impacts. The definition of the functional unit (FU) within LCA can significantly influence the results, affecting the assessment of greenhouse gas (GHG) emissions and, consequently, the selection of asphalt mixtures. In this context, this study aims to analyze the impact of different functional units on the selection of asphalt mixtures for road pavements, considering the phases of raw material extraction, material production, mixing, and construction. To this end, the mechanical behavior of two distinct asphalt mixtures was evaluated under two different loading conditions, and their contributions to climate change were assessed using three functional units: t CO₂ eq/km of roadway, kg CO₂ eq/t of HMA, and kg CO₂ eq/m³ of HMA. The results indicated that asphalt mixtures with a higher resilient modulus require thinner pavement layers, leading to lower GHG emissions. However, when asphalt mixtures are analyzed individually and compared, no clear pattern in GHG emissions is observed, reflecting the specific characteristics of each production process. Additionally, it was found that the environmental impact varied according to the adopted functional unit, demonstrating that this choice can significantly influence decision-making regarding the selection of asphalt mixtures in terms of their contributions to climate change. It was concluded that the selection of the FU in pavement LCA should be aligned with the study's objective and the context of the analysis, as an inadequate choice may compromise the selection of asphalt mixtures.